Understanding the impact of multinational military interventions on the status of local women. A case study analysis of Afghanistan, Iraq and Libya - Mutongerwa, Rumbidzayi Victoria (University of the Witwatersrand, Johannesburg, 2024)
The research analyses the impact of multinational military intervention on local women’s status in Afghanistan (2001), Iraq (2003) and Libya (2011). Women are the study's primary focus because they are disproportionately impacted by violent conflict, which exacerbates already-existing prejudice and gender inequities. Their political, economic, educational, healthcare and security status are analysed. The research examines their status in the two years before the interventions, during the occupation and one year after the withdrawal of troops. The before and after case study method is used in the analysis. This method compares observations made before and after the implementation of an intervention to determine the impact of the intervention. The Gender Development Index, Gender Inequality Index and the Women’s Political Empowerment Index are used in the analysis. Gender disparities in human development are measured by the Gender Development Index (GDI) in three main areas: education (mean and projected years of schooling), economic position (estimated earned income), and health (life expectancy). A greater GDI denotes less gender gaps and better overall gender equality. The Gender Inequality Index (GII) gauges gender-based disparities in three important domains: economic activity (labor market participation rates), empowerment (the share of women holding parliamentary seats and women’s educational attainment in secondary and higher education), and reproductive health (the maternal mortality ratio and adolescent birth rates). Greater gender disparity in these domains is indicated by a higher GII score. The V-Dem Women's Political Empowerment Index assesses women's political empowerment by examining their involvement and representation in political processes, access to power and resources, and influence over political decisions. It considers issues such as women's suffrage, representation in parliament, and the degree to which women can participate in civil society groups and influence policymaking. The research finds that while some improvements to women’s status were made during the occupation period, women’s status mainly diminished after withdrawal. The study recommends that in future, intervening states should consider the long-term effects of interventions on women, understand the cultural contexts of target states before intervention, promote transparency and accountability concerning policy initiatives and programs and involve women in the peace and security processes.
A research report submitted in fulfillment of the requirements for the Degree of Master of Arts (International Relations) , In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; multinational military; local women; Afghanistan; Iraq and Libya; SDG-17: Partnerships for the goals